The Effect Of Health Care Service Quality On BPJS Outpatient Patient Satisfaction At Undata Regional Public Hospital, Palu City, Central Sulawesi Province - Herdhana Suwartono; Syamsuriyati, Syamsuriyati; Anwar Ramli (Sean Institute, 2024)
Health is a basic need that must be guaranteed by the state as mandated by the 1945 Constitution. The government developed the JKN program through BPJS Kesehatan so that people, including the economically weak, can access health services. RSUD Undata Palu, as a type B referral hospital, faces the challenge of meeting the increasing needs of outpatients. This study aims to analyze the effect of health worker service quality on outpatient BPJS patient satisfaction at RSUD Undata Palu. Using a quantitative approach with a cross-sectional survey design, data was collected from 175 BPJS outpatients using a questionnaire, which was analyzed using validity, reliability, and SEM tests. The results showed that service quality was in the “good” category (mean score 4.22), with the reliability dimension recording the highest score (4.35). The level of patient satisfaction was also rated as “good” (mean score 4.30), with medical services being the best indicator (4.40). SEM analysis showed that service quality had a significant effect on patient satisfaction, with reliability contributing the most (β = 0.35). This study confirms the importance of reliability, responsiveness, and competence of health workers in improving patient satisfaction. RSUD Undata is advised to increase service speed, provide effective communication training, and improve the physical facilities of the hospital. These findings support previous literature and are expected to make theoretical as well as practical contributions to the development of health service quality and the success of the JKN program.